The Influence of Family Environment on Elementary School Students’ Learning Achievement - Lubis, Via Ranzani; Afridannur, Wafiah (International Journal of Students Education, 2023)
Achievement is the result of an activity that someone has done. Meanwhile, learning achievement is defined as the results of assessments obtained from cognitive school activities and is usually determined through measurement and assessment. Student learning achievement is influenced by several factors, namely external factors and internal factors. Learning motivation is one of the internal factors of student learning achievement, while the family environment and the role of parents are external factors that influence student learning achievement. Achievement is the result that a person has achieved in carrying out activities. Improving student learning achievement is not easy because there are many factors that influence the learning process therein. These factors are the reasons why students get grades below the KKM. Students feel that the family environment and surroundings of the school are comfortable and supportive, which can increase students’ enthusiasm and willingness to learn and improve their achievements. The aim to be achieved in this research is to find out whether there is an influence of the family environment on the learning achievement of class IV A students at SD Inpres Mangga Dua Merauke. This type of research uses literature review research. Literature review is an activity of analyzing reading which can be in the form of criticism of research being carried out on a special topic which is part of a scientific field. Literature research process by reviewing literature and analyzing relevant topics. The results of the research show that there is a large influence of the family environment on the learning achievement of class IV A students at SD Inpres Mangga Dua Merauke. The family environment has a strong positive relationship with student learning achievement with a correlation value of 0.673. The magnitude of the influence of the family environment on student learning achievement is 45.2%.